Optimalisasi Peran Masjid Sebagai Pusat Pendidikan dan Pemberdayaan Ummat - Supyan, Asri; Aidil Adha, Muhammad; Arba’i, Wahid; Wahyudi, Ihsan; Sabri, Muhammad; Arifin, Zainul; Wati, Jusrida; Sa'diah, Halimatus; Alawiyah, Faizah; Adawiyah, Rabiatul (LP2M STAI Darul Kamal NW Kembang Kerang-NTB, 2024)
This community service program aims to improve the prosperity of the mosque, especially in increasing the participation of the congregation in religious activities and to improve the knowledge and understanding of the Dasan Lendang hamlet community regarding the optimization of the role of the mosque. This Community Service activity uses the Participatory Action Research (PAR) approach. The method used in this service is Socialization and mentoring. The results of this service, there are several activities carried out to optimize the role of the mosque, namely: socialization through studies and lectures held twice a week every Thursday and Sunday nights, discussions and questions and answers held once a week every Tuesday night, providing assistance in reading the barzanjian which is held once a week every Monday night, and the yasinan which is held once a week every Friday night. With the implementation of socialization and mentoring, the mosque management has become more active and has made the mosque more alive, for children, youth and parents. So that the mosque becomes a place for various activities for the community.